2019
DOI: 10.1111/1541-4337.12450
|View full text |Cite
|
Sign up to set email alerts
|

Processing, Nutrition, and Functionality of Hempseed Protein: A Review

Abstract: The increasing demand for plant proteins, along with rising awareness of the nutritional and functional roles of dietary proteins, has prompted the nutrition and food industry to explore nontraditional protein sources. Hempseed protein with its excellent nutritional value and superior digestibility has drawn great interest in both scientific and industrial fields. In this review, the chemistry and nutritional quality of hempseed protein and the health benefits of bioactive peptides derived thereof are highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
117
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(119 citation statements)
references
References 85 publications
2
117
0
Order By: Relevance
“…The above results indicated that all the three processes were able to convert HPB into products with antioxidant properties, though the mechanisms responsible of the observed activities cannot be defined at this stage of research. Antioxidant properties have been previously reported for hemp seed protein hydrolysates obtained by enzymatic treatment of protein extracts (Tang et al 2009;Girgih et al 2013;Wang and Xiong 2019). On a similar experiment conducted on rapeseed protein hydrolysates, the EC50 was 0.71 mg/mL, similar to what we found in HPB prior microbial hydrolysis (Pan et al 2011).…”
Section: Antioxidant Capacity Of Biorefinery Productssupporting
confidence: 87%
“…The above results indicated that all the three processes were able to convert HPB into products with antioxidant properties, though the mechanisms responsible of the observed activities cannot be defined at this stage of research. Antioxidant properties have been previously reported for hemp seed protein hydrolysates obtained by enzymatic treatment of protein extracts (Tang et al 2009;Girgih et al 2013;Wang and Xiong 2019). On a similar experiment conducted on rapeseed protein hydrolysates, the EC50 was 0.71 mg/mL, similar to what we found in HPB prior microbial hydrolysis (Pan et al 2011).…”
Section: Antioxidant Capacity Of Biorefinery Productssupporting
confidence: 87%
“…Hemp ( Cannabis sativa L.) is a multiuse crop grown primarily for grain, fiber, and cannabinoids. In recent years, there has been a resurgence in the study of hemp in the United States and across the world in fields including genomics (Grassa et al, ; Laverty et al, ), agronomics (Campbell, Berrada, Hudalla, Amaducci, & McKay, ), and novel end‐uses (Turner, Sloan, & Currell, ; Wang & Xiong, ). The market for hemp (defined as <0.3% tetrahydrocannabinol; THC by dry weight) and marijuana (>0.3% THC), is expected to surpass $26 billion in the US by 2025 (Global Cannabis Report: 2019 Industry Outlook, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is an increasing interest in using locally cultivated hemp seeds as a raw material for food production. Hemp seeds, the by-product from the fibre use for the construction industry, are rich in fats (25-35%, mostly unsaturated fatty acids), proteins (20-25%), dietary fibre (10-15%), vitamins, and minerals [16].…”
Section: Introductionmentioning
confidence: 99%